2017
DOI: 10.1186/s12879-017-2388-7
|View full text |Cite
|
Sign up to set email alerts
|

Digital CXR with computer aided diagnosis versus symptom screen to define presumptive tuberculosis among household contacts and impact on tuberculosis diagnosis

Abstract: BackgroundHousehold (HH) contact tracing is a strategy that targets high risk groups for TB. Symptom based screening is the standard used to identify HH contacts at risk for TB during HH contact tracing for TB. However, this strategy may be limited due to poor performance in predicting TB. The objective of this study was to compare CXR with Computer Aided Diagnosis (CAD) against symptom screen for defining presumptive TB and how TB detection changes with each method.MethodsHousehold contacts of consecutive ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…While CXR accessibility may be limited and can cost up to 20 USD in some high burden countries [ 25 ], in many Asian settings it is widely available, relatively inexpensive and used extensively in the private sector [ 8 , 26 ]. While a plethora of studies have been published on different ways to improve TB case detection including improved outreach [ 27 , 28 ], systematic screening in facilities [ 29 ], more sensitive diagnostics [ 30 ], strengthening public-private links [ 31 ], as well as contact investigation [ 20 ], there have been only a handful of published studies that have evaluated the impact of using CXR in addition to symptom screening for TB outside of prevalence surveys [ 11 – 13 ]. Two of these studies were done in high HIV burden settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While CXR accessibility may be limited and can cost up to 20 USD in some high burden countries [ 25 ], in many Asian settings it is widely available, relatively inexpensive and used extensively in the private sector [ 8 , 26 ]. While a plethora of studies have been published on different ways to improve TB case detection including improved outreach [ 27 , 28 ], systematic screening in facilities [ 29 ], more sensitive diagnostics [ 30 ], strengthening public-private links [ 31 ], as well as contact investigation [ 20 ], there have been only a handful of published studies that have evaluated the impact of using CXR in addition to symptom screening for TB outside of prevalence surveys [ 11 – 13 ]. Two of these studies were done in high HIV burden settings.…”
Section: Discussionmentioning
confidence: 99%
“…While Xpert has been well established as a more sensitive test than smear microcopy [ 10 ], few studies have looked at the value of combined screening approaches settings outside of prevalence surveys. A couple recent studies showing the value of CXR screening over symptom screening in clinic or hospital settings [ 11 , 12 ] and one in contact investigation [ 13 ], but the data is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The yield could have been higher if x-rays had been used as a screening tool and GeneXpert used as a diagnostic tool for all. As an example, in a study in Zambia, out of all contacts screened with chest x-ray, 53.6% had abnormal chest x-rays, and out of those, TB (all forms) was diagnosed in 32%; 19% of them were bacteriologically confirmed, but 8% had no symptoms [ 19 ]. Chest x-ray is highly sensitive, and most of the TB cases identified in national prevalence surveys and focal studies were found by chest x-ray rather than by symptomatic screening alone [ 17 – 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, in a study in Zambia, out of all contacts screened with chest x-ray, 53.6% had abnormal chest x-rays, and out of those, TB (all forms) was diagnosed in 32%; 19% of them were bacteriologically confirmed, but 8% had no symptoms [19]. Chest x-ray is highly sensitive, and most of the TB cases identified in national prevalence surveys and focal studies were found by chest x-ray rather than by symptomatic screening alone [17][18][19][20]. GeneXpert is also a more sensitive and specific tool for TB diagnosis [20,21].…”
Section: Plos Onementioning
confidence: 99%
“…In a recent study of diagnostic accuracy of chest radiographs, sensitivity ranged from 61 to 94% and specificity from 20 to 48% in assessments by pediatric radiologists and pulmonologists (49). While the introduction of a chest radiograph reading and recording system showed minimal value (50), the use of digital chest radiographs with computer aided diagnosis may improve its diagnostic value, particularly in the asymptomatic contact and eliminating the need for specialist interpretation (51).…”
Section: Tb Diagnosismentioning
confidence: 99%